2020
DOI: 10.2147/dmso.s268481
|View full text |Cite
|
Sign up to set email alerts
|

<p>Barriers to Self-Management of Type 2 Diabetes During COVID-19 Medical Isolation: A Qualitative Study</p>

Abstract: Purpose: Diabetes self-management behaviors are necessary to obtain optimum glycemic control, reduce the risk of complications, and improve health outcomes. The COVID-19 pandemic imposes an additional struggle for self-management by diabetes patients. Although previous studies have reported socio-demographic, behavioral, psychological, and cultural barriers to diabetes self-management, little is known about perceived barriers to diabetes self-management among patients during isolation following their recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 52 publications
3
73
0
1
Order By: Relevance
“…It was found that the fasting blood sugar values of individuals in the control group were higher than those of individuals in the intervention group. Also, although no significant difference was found in diastolic and sistolic blood pressure values in the control group in the COVID-19 pandemic compared with the beginning, a significant decrease was seen in the intervention group [3]. Thus, it can be said that the traditional face-to-face medical treatment needs of the individuals with type 2 diabetes participating in our study could not be met.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…It was found that the fasting blood sugar values of individuals in the control group were higher than those of individuals in the intervention group. Also, although no significant difference was found in diastolic and sistolic blood pressure values in the control group in the COVID-19 pandemic compared with the beginning, a significant decrease was seen in the intervention group [3]. Thus, it can be said that the traditional face-to-face medical treatment needs of the individuals with type 2 diabetes participating in our study could not be met.…”
Section: Discussionmentioning
confidence: 61%
“…In order to protect themselves during the outbreak, diabetic patients are spending more time indoors. Measures taken during the COVID-19 pandemic, isolation and social distancing restrictions have made it difficult for people with diabetes to exercise regularly and remain physically active [3,6]. In this time, many diabetics have chosen to delay or cancel their health service appointments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations